(untitled) (Nordic Journal of African Studies, 2008)
Most researchers on adolescent reproductive health and related susceptibility to contracting HIV/AIDS have highlighted the ironical mismatch preponderant between adolescent knowledge of HIV/AIDS transmission dynamics and behavioural change exemplified in part by abstinence but also condom use. The paradox is compounded by the fact that survey data seems to depict heightened knowledge of the dynamics per se. Empirical data has previously posited variables as peer pressure and other psychosocial factors as the crisis at adolescence as explaining the anomaly. Results in the current study however unveil the culture of silence; the disdain towards AIDS messages and retrogressive cultural practices as alternative explanation. The results were obtained through survey data from adolescent students in selected schools in Zomba, a district in southern Malawi, and are discussed within the larger context of the applicability of cognitive dissonance theory to the AIDS pandemic.